(3GdJgPjHs - (3GdMSjf Hf eSYhO Hf eMeO, GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, GdHZhj,J (B510 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdbUGU HGH JMQje GdbJd hef Ydjg GdbUGU s
(3BNQgG (B:s
(3HGH GdMce aj GdSGMQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B61s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B517s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYj (B488) s
Keywords: (3Gdabg GdTGaYjs